Loci sacri understanding sacred places. - Bell, David N. 1943-; Caspers, Charles 1953-; Coomans, Thomas; De Dijn, Herman; Delbeke, Maarten; Heynickx, Rajesh; Jones, Lindsay 1954-; Kinder, Terryl N.; Maeyer, Jan de.; Morisset, Lucie K.; Noppen, Luc; Scott, J. S. (James S.); et al. (Leuven University press, 2012)
Sacred places have long exercised a special fascination. Sacred places are not static entities but reveal a historical dynamic. They are the result of cultural developments and have varied multidimensional levels of significance. They are places where time is, as it were, suspended, and they are points where holy times and holy places meet. Sacred places are places apart. It is this specificity in the context of the Christian religions of the West that 'Loci sacri' wishes to unveil by bringing together specialists from various disciplines, countries, and Christian denominations. One of the questions is why some sites have for centuries proven to be so popular while others have not. Another topic is the way in which extraordinary natural sites have been designated as sacred and given new meaning, primarily by means of architecture. "Loci sacri" also explores the 'eternal' character of this sacred status.
Keywords: Christianity; Religious facilities; Sacred space; Shrines; 203.5 -- Religion Public worship and other practices Sacred places and pilgrimages; 291 <063> -- Godsdienstwetenschap: vergelijkend--Congressen; 291.35 -- Heilige plaatsen: altaren; tempels; pagoden; kerken; moskeeën; bossen; grotten; heilige landen en steden